Answer

Verified

380.4k+ views

**Hint:**For this question, we will directly use the formula of first derivative principle to find the derivative. The formula is given below as: \[f'\left( x \right) = \mathop {\lim }\limits_{h \to 0} \dfrac{{f\left( {x + h} \right) - f\left( x \right)}}{h}\]. So, use this concept to reach the solution of the given problem.

**Complete step by step answer:**

We have to find out the derivative of \[\tan x\]. So, our function will be \[f\left( x \right) = \tan x\].

According to the first derivative principle, we have

\[

\Rightarrow f'\left( x \right) = \mathop {\lim }\limits_{h \to 0} \dfrac{{\tan \left( {x + h} \right) - \tan x}}{h} \\

\Rightarrow f'\left( x \right) = \mathop {\lim }\limits_{h \to 0} \dfrac{{\dfrac{{\sin \left( {x + h} \right)}}{{\cos \left( {x + h} \right)}} - \dfrac{{\sin x}}{{\cos x}}}}{h}{\text{ }}\left[ {\because \tan A = \dfrac{{\sin A}}{{\cos A}}} \right] \\

\]

Taking LCM and simplifying further, we have

\[ \Rightarrow f'\left( x \right) = \mathop {\lim }\limits_{h \to 0} \dfrac{{\sin \left( {x + h} \right)\cos x - \cos \left( {x + h} \right)\sin x}}{{h\cos x\cos \left( {x + h} \right)}}\]

By using the formula, \[\sin A\cos B - \cos A\sin B = \sin \left( {A - B} \right)\], we have

\[

\Rightarrow f'\left( x \right) = \mathop {\lim }\limits_{h \to 0} \dfrac{{\sin \left( {x + h - x} \right)}}{{h\cos x\cos \left( {x + h} \right)}} \\

\Rightarrow f'\left( x \right) = \mathop {\lim }\limits_{h \to 0} \dfrac{{\sin \left( h \right)}}{{h\cos x\cos \left( {x + h} \right)}} \\

\]

Splitting the limits, we have

\[ \Rightarrow f'\left( x \right) = \mathop {\lim }\limits_{h \to 0} \dfrac{{\sin \left( h \right)}}{h} \times \mathop {\lim }\limits_{h \to 0} \dfrac{1}{{\cos x\cos \left( {x + h} \right)}}\]

By using the formula, \[\mathop {\lim }\limits_{x \to 0} \dfrac{{\sin x}}{x} = 1\], we have

\[ \Rightarrow f'\left( x \right) = \mathop {\lim }\limits_{h \to 0} \dfrac{1}{{\cos x\cos \left( {x + h} \right)}}\]

We know that for \[h \to 0\] we have \[\cos \left( {x + h} \right) \simeq \cos x\]

\[

\Rightarrow f'\left( x \right) = \dfrac{1}{{\cos x\cos x}} \\

\Rightarrow f'\left( x \right) = \dfrac{1}{{{{\cos }^2}x}} \\

\therefore f'\left( x \right) = {\sec ^2}x\,{\text{ }}\left[ {\because \sec x = \dfrac{1}{{\cos x}}} \right] \\

\]

**Thus, the derivative of \[\tan x\] using the first derivative principle is \[{\sec ^2}x\].**

**Note:**Using the first derivative method, it consumes much time. And for smaller functions, we can find out the derivative using the first derivative method. But if the function is complex, then it is too difficult to solve using this method. Then we follow conventional methods for finding the derivative.

Recently Updated Pages

The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths

How do you arrange NH4 + BF3 H2O C2H2 in increasing class 11 chemistry CBSE

Is H mCT and q mCT the same thing If so which is more class 11 chemistry CBSE

What are the possible quantum number for the last outermost class 11 chemistry CBSE

Is C2 paramagnetic or diamagnetic class 11 chemistry CBSE

What happens when entropy reaches maximum class 11 chemistry JEE_Main

Trending doubts

How do you solve x2 11x + 28 0 using the quadratic class 10 maths CBSE

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

Difference Between Plant Cell and Animal Cell

Give simple chemical tests to distinguish between the class 12 chemistry CBSE

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

How will you bring about the following conversions class 12 chemistry CBSE

Consider a system of two identical particles One of class 11 physics CBSE

Change the following sentences into negative and interrogative class 10 english CBSE

State the laws of reflection of light